Penggunaan E-wallet dan E-commerce dalam Belanja Pangan dan Non-Pangan Mahasiswa - Dewani, Luh Ayu Karunia; Susrusa, Ketut Budi; Arisena, Gede Mekse Korri; Bakhtiar, Ary (Universitas Galuh, 2026)
Advances in digital technology have driven changes in student consumption patterns, particularly through the use of e-wallets and e-commerce as the primary means of transaction. The ease of access, speed of processing, and variety of promotions have made digital platforms an important part of consumption activities, including purchases that are not always based on actual needs. This situation has given rise to a tendency toward consumerism among students. This study aims to analyze the relationship between the use of e-wallets and e-commerce and the level of consumerism among students in the purchase of food and non-food products. The approach used is quantitative, with descriptive analysis to map the characteristics of respondents and Spearman's Rho correlation test to measure the relationship between variables. Data was collected through a questionnaire administered to active users of digital platforms. The results show that the majority of respondents have a high frequency of using e-wallets and e-commerce, with ready-to-eat food and personal care products being the dominant categories. The correlation test shows a relationship between the use of digital platforms and the level of consumerism among students. These findings highlight the importance of strengthening financial and digital literacy to encourage more rational and sustainable consumption behavior among students.